2013
DOI: 10.2478/pjs-2013-0069
|View full text |Cite
|
Sign up to set email alerts
|

Radial Wrist Extensors as a Dynamic Stabilizers of Scapholunate Complex

Abstract: Wrist stabilization is ensured by the complex of stabilizers, both static (intrinsic and extrinsic ligaments) and dynamic ones (flexor and extensor sinews of the wrist). Extrinsic carpal ligaments link both carpal rows with forearm, while the intrinsic ones connect individual carpal bones. From among intrinsic ligaments, the most significant from clinical point of view is scapholunate ligament (scapholunate lig. -SL). Instability of the SL resulting from SL ligament tear is the most frequent type of carpal ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In our study we have found that rotatory subluxation of the scaphoid can also occur with incomplete SLIL lesion. In the new classification this injury can be present at both I b and III a (Garcia-Elias stage IV) stages, depending on the ability of primary repair of SLIL lesion [3,[10][11][12]20,21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study we have found that rotatory subluxation of the scaphoid can also occur with incomplete SLIL lesion. In the new classification this injury can be present at both I b and III a (Garcia-Elias stage IV) stages, depending on the ability of primary repair of SLIL lesion [3,[10][11][12]20,21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…That is the reason why in numerous cases of SL instability SL angle will exceed 80° [3,10,11]. For rotatory subluxation of the scaphoid the radio scaphoid angle (≤45°) will be more typical [20,21]. Finally, we speak about the last stage (IV°) when any degenerative changes occur.…”
Section: Gr Up Smmentioning
confidence: 97%
See 2 more Smart Citations
“…2a ). A PA clenched fist view may show greater than 5 mm of widening between the scaphoid and lunate (Terry Thomas sign) is diagnostic of a complete SL ligament tear [ 13 ]. Chronic tears may demonstrate a static SL gap on the PA film and an increased SL angle on the lateral consistent with dorsal intercalated segmental instability (DISI).…”
Section: Introductionmentioning
confidence: 99%